Teradata physical database design - Coffing, Tom (Tera-Tom genius series ;, 2013)
The design of the data warehouse is the most important aspect, so this book is a fantastic guide on exactly how to do just that. This book brilliantly touches on the important things a designer needs to do to build a world-class data warehouse. They will clearly understand the environment and all options to enhance the performance based on the design. This will teach you great detail in a high-level manor that really focuses clearly so you won't get bogged down with too much minutia. It will allow you to understand the important issues so you can make clear decisions.